Processing of monazite leach liquor for the recovery of light rare earth metals (LREMs). (December 2018) - Kumari, Archana; Jha, Soni; Patel, Jay Narayan; Chakravarty, Sanchita; Jha, Manis Kumar; Pathak, Devendra Deo
Graphical abstract: Highlights: Novel process to recover LREMs from monazite leach liquor. LREMs oxide of high purity is obtained using hydrometallurgical technique. Complete process flow-sheet for the production of non-ferrous and LREMs. Abstract: Due to diverse applications of light rare earth metals (LREMs) oxides in advanced electronics and material/alloy, the recovery of pure LREMs oxides from the rare earth metals (REMs) mixture is one of the important areas of separation science. Present paper reports the systematic and selective precipitation studies to produce pure oxides of LREMs from the leach liquor of Korean monazite. Various process parameters like precipitant dose, pH of the solution, temperature and time were varied for obtaining the optimal conditions for the selective precipitation of pure LREMs from leach liquor which contains REMs and other metallic impurities. The use of 4 g/L of disodium oxalate (Na2 C2 O4 ) was found to be suitable to precipitate 98.10% of pure LREMs leaving unwanted metals in solution within 10 min when maintaining pH < 1 at room temperature. The Eh-pH diagram satisfactorily validated the obtained experimental data for LREMs recovery. The collected precipitate of LREMs as oxalate was converted to oxide at elevated temperature 400 °C in 3 h. Based on the experimental results, a flow-sheet has been proposed for the production of pure LREMs oxide from monazite leach solution. Based on the laboratory scale proof of concept and validations, the process seems to be feasible for commercial exploitation after scale-up/ pilot trials.